Representation of Traumas of Displacement in Marie Therese Toyis Weep Not, Refugee - Astelia Mihayo; Stanley Elias (Journal of Language and Literature, 2019)
With the ever-increasing outbreak of intrastate and interstate wars since the mid-20th century, Africa has experienced mass displacement of people which has subsequently resulted in an increase of displaced communities in the world. From these displaced communities, African refugees constitute a significant share of the total displaced people in the globe, which count to 68.5 million people. The present study explored representation of traumas of displacement in Marie Therese Toyis Weep Not, Refugee. The study deployed Ruth Caruths tenets of trauma studies in literature. The findings of the study affirm the authors use Weep Not Refugee to explore the significant contribution of displacement to delineate and circumscribe Burundian refugees with traumatised and reduced identities in areas of displacement. In most cases, the journey of leaving home and later their lives in refuge of Burundians are explicated to be surrounded by tragic experience and reduced identities that ascribe them to burden and non-entity beings. Moreover, the authors provide an opportunity for readers to explore displacement and its significant contribution to the constructions of cultural trauma among refugees. Because of ethnic war which has led to displacement of Burundians to other areas, Burundians have to lose some cultural aspects and invent new ones for the sake of cultural adjustment in the foreign land they are hosted.Keywords: displacement, reduced identities, trauma